Prevalence of Pharmaceuticals in Surface Water Samples in Ghana - David Azanu; David Adu-Poku; Selina Ama Saah; William Ofori Appaw (Journal of Chemistry)
Pharmaceuticals, among the emerging contaminants, are pseudopersistent and recently of serious concern due to universal use, toxicity, and resistance development at low concentrations. This study was aimed at assessing the prevalence and risk of eight pharmaceuticals in surface water used for vegetable irrigation in Ghana’s Kumasi and Sunyani metropolises, which are influenced by hospitals, sewage treatment facilities, and market effluents. Samples were concentrated via solid-phase extraction (SPE) while liquid chromatography was used to identify and quantify the analytes. Ibuprofen, acetaminophen, and diclofenac were the detected analgesics in this study, with concentrations stretching from below detection limit (not detected) to 319.0 ng/L, while amoxicillin, trimethoprim, and cefuroxime were the detected antibiotics with a concentration range of no detection to 840.0 ng/L. Based on the available long-term data, an environmental risk assessment was conducted. Because of the presence of ibuprofen, the lowest trophic level and fish were shown to be at risk. The estimated risk quotient values for antibiotics resistance were above 1 for all the antibiotics investigated in surface water impacted by the wastewater of hospitals and pharmaceutical companies’ except surface water impacted by sewage treatment plants (STPs) and market wastewater. The existence of these pharmaceuticals in surface water does not only point to a general concern for the environment but also a potential health risk on humans and other lives as a result of their impact on drinking water and vegetable production in Ghana.